The Effect of Octopamine on the Locust Stomatogastric Nervous System - Rand, David; Knebel, Daniel; Ayali, Amir (Frontiers in Physiology, 2012)
Octopamine (OA) is a prominent neuromodulator of invertebrate nervous systems, 33 influencing multiple physiological processes. Among its many roles in insects are the 34 initiation and maintenance of various rhythmic behaviors. Here, the neuromodulatory 35 effects of OA on the components of the locust stomatogastric nervous system (STNS) 36 were studied, and one putative source of OA modulation of the system was identified. 37 Bath application of OA was found to abolish the endogenous rhythmic output of the 38 fully isolated frontal ganglion (FG), while stimulating motor activity of the fully 39 isolated hypocerebral ganglion (HG). OA also induced rhythmic movements in a 40 foregut preparation with intact HG innervation. Complex dose-dependent effects of 41 OA on interconnected FG-HG preparations were seen: 10-5M OA accelerated the 42 rhythmic activity of both the HG and FG in a synchronized manner, while 10-4M OA 43 decreased both rhythms. Intracellular stimulation of an identified octopaminergic 44 dorsal unpaired median (DUM) neuron in the subesophageal ganglion (SEG) was 45 found to exert a similar effect on the FG motor output as that of OA application. Our 46 findings suggest a mechanism of regulation of insect gut patterns and feeding-related 47 behavior during stress and times of high energy demand.